Identification of sequence polymorphisms in the D-Loop region of mitochondrial DNA as a risk factor for colon cancer. (1st November 2016) - Guo, Zhanjun; Zhao, Shengnan; Fan, Haiyan; Du, Yanming; Zhao, Yufei; Wang, Guiying
Abstract: The accumulation of single nucleotide polymorphisms (SNPs) in the displacement loop (D-Loop) of mitochondrial DNA (mtDNA) has been identified for their association with cancer risk in a number of cancers. We investigated the colon cancer risk profile of D-Loop SNPs in a case–control study. The frequent alleles of nucleotides 73G/A, 146T/C, 195T/C, 324C/G, 16261C/T, and 16304T/C as well as the minor allele of 309C/C insert were significantly associated with an increased risk for colon cancer. In conclusion, SNPs in the mtDNA D-Loop were found to be valuable markers for colon cancer risk evaluation.